A Trioethnography of Organic Mentoring in the Doctoral Process. Issue 4 (8th August 2021) - Rogers-Shaw, Carol; Carr-Chellman, Davin; Choi, Jinhee
ABSTRACT: As three academic researchers resisting the existing recognition order through generative, non-instrumentalizing relationships, we represent a substantive move away from the prevailing developmental model of doctoral student preparation. We highlight the struggle against misrecognition in the academy. Drawing on duoethnographic methods, we explore the nature of doctoral study and effective approaches to mentoring doctoral students as future researchers and university faculty. We contribute to the literature on mentoring non-traditional adult learners in higher education by defining organic mentoring as non-instrumental, relational, and collaborative. Additionally, we extend the use of duoethnography to trioethnography by involving three researchers in dialogic storytelling to illuminate overlapping experiences from different angles. Lastly, we further develop the use of Axel Honneth's recognition theory by linking it to adult mentoring in doctoral study.